Supporting dataset for Extended range and aberration-free autofocusing via remote focusing and sequence-dependent learning - Jiahe Cui; Turcotte, R; Emptage, N; Booth, M (University of Oxford, 2022)

(untitled)
Extended range and aberration-free autofocusing via remote focusing and sequence-dependent learning Jiahe Cui, Raphael Turcotte, Nigel J. Emptage, Martin J. Booth https://doi.org/10.1364/OE.442025